Prediction of Risk Factors for the Evolution of Traumatic Subdural Effusion into Chronic Subdural Hematoma - Chen S (Dove Medical Press, 2020)
Sansong Chen,1 Hui Peng,2 Xuefei Shao,1 Lin Yao,1 Jie Liu,1 Jiongping Tian,1 Lean Sun,1 Yi Dai,1 Xiaochun Jiang,1,* Limin Cheng3,* 1Department of Neurosurgery, The First Affiliated Hospital of Wannan Medical College (Yijishan Hospital), Wuhu 241001, Anhui, People’s Republic of China; 2Administration Office of Hospital Admission and Discharge, The First Affiliated Hospital of Wannan Medical College (Yijishan Hospital), Wuhu 241001, Anhui, People’s Republic of China; 3Morphology Experiment & Training Center, School of Preclinical Medicine, Wannan Medical College, Wuhu 241002, Anhui, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaochun JiangDepartment of Neurosurgery, The First Affiliated Hospital of Wannan Medical College (Yijishan Hospital), Wuhu 241001, Anhui, People’s Republic of ChinaEmail jiangxiaochun2001@hotmail.comLimin ChengMorphology Experiment & Training Center, School of Preclinical Medicine, Wannan Medical College, Wuhu 241002, Anhui, People’s Republic of ChinaEmail 630336548@qq.comPurpose: To explore the risk factors of the evolution of traumatic subdural effusion (TSE) into chronic subdural hematoma (CSDH).Materials and Methods: The 70 patients’ gender, age, location of effusion, unilateral and bilateral, Glasgow coma score (GCS) at admission, presence or absence of brain contusion, the time of effusion appeared, daily amount of mannitol, mannitol number of days used, with or without atorvastatin calcium tablets, with or without antiplatelet aggregation drugs, with or without anticoagulant drugs, with or without abnormalities in blood coagulation routines, computed tomography (CT) layer height, the thickness, and CT value of the first effusion were analyzed by single factor. Logistic multivariate regression analysis was performed on the statistically significant indicators. Power of the regression model was evaluated using receiver operating characteristic (ROC) curve.Results: Univariate analysis showed that the presence or absence of brain contusion, the time of effusion appeared, atorvastatin calcium tablets use or not, the CT value of the effusion, and TSE into CSDH evolution varied significantly compared to the non-evolved group (P< 0.05). Logistic multivariate regression analysis showed that combined brain contusion (odds ratio (OR)=16.247, 95% confidence interval (CI), 1.831– 144.157, P = 0.012), early onset of effusion (OR = 0.573, 95% CI: 0.349– 0.941, P = 0.028), atorvastatin calcium tablets not used after effusion (OR = 60.028, 95% CI: 6.103– 590.399, P = 0.0001), and high CT value (OR = 1.285, 95% CI: 1.067– 1.547, P = 0.008) were risk factors for the evolution of TSE into CSDH. The ROC model suggested that the prediction of these risk factors had high diagnostic accuracy.Conclusion: TSE patients with brain contusion, early onset of effusion, without the usage of atorvastatin calcium tablets after effusion, and high CT value of the first effusion are at a risk of evolving into CSDH.Keywords: TSE, CSDH, evolution, risk factors